2012
DOI: 10.1128/mbio.00159-12
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Derived Human Intestinal Organoids as an Infection Model for Rotaviruses

Abstract: ABSTRACTDirected differentiation of stem cell lines into intestine-like tissue called induced human intestinal organoids (iHIOs) is now possible (J. R. Spence, C. N. Mayhew, S. A. Rankin, M. F. Kuhar, J. E. Vallance, K. Tolle, E. E. Hoskins, V. V. Kalinichenko, S. I. Wells, A. M. Zorn, N. F. Shroyer, and J. M. Wells, Nature 470:105-109, 2011). We tested iHIOs as a new model to cultivate and study fecal viruses. Protocols for infection of iHIOs with a laboratory strain of rotavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
190
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(199 citation statements)
references
References 25 publications
(31 reference statements)
2
190
0
2
Order By: Relevance
“…To date, human enteroids have been shown to model human RV infection, cholera toxin effect on transport, and several aspects of enterohemorrhagic Escherichia coli-related human diarrhea (9). RV replicates and produces infectious virus in human enteroids and organoids, with viral replication increasing over 96 h (13,36). Rotavirus infection causes very rapid inhibition of NHE3, which might be a significant contributor to RV-induced diarrhea, the pathophysiology of which remains poorly understood (37).…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
“…To date, human enteroids have been shown to model human RV infection, cholera toxin effect on transport, and several aspects of enterohemorrhagic Escherichia coli-related human diarrhea (9). RV replicates and produces infectious virus in human enteroids and organoids, with viral replication increasing over 96 h (13,36). Rotavirus infection causes very rapid inhibition of NHE3, which might be a significant contributor to RV-induced diarrhea, the pathophysiology of which remains poorly understood (37).…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
“…Lgr5 + intestinal crypt stem cells differentiate into the various epithelial cell subtypes found in the human small intestine in vivo, resulting in the production of enteroid structures over 4 to 5 days (11). Others have shown that human enteroids can serve as models for the study of enteric infections by human rotavirus (12,13) and norovirus (14).…”
mentioning
confidence: 99%
“…This is even more apparent in PhoP mutants . Gastrointestinal viruses cause a large part of the yearly estimated 1.7 billion cases of acute diarrhea (Finkbeiner et al, 2012). Next to norovirus, rotavirus, a double-stranded RNA virus of the family Reoviridae, is the most common cause of diarrhea in young children.…”
Section: Anaerobic Bacteriamentioning
confidence: 99%